(untitled) (Physical Education, Health and Social Sciences, 2026)
Background: Total Knee Arthroplasty is a highly effective operation for reducing pain and impairment caused by advancing osteoarthritis of the knee. Total knee arthroplasty results are routinely measured using quality of life tools. Objective: The objective of this study was to determine the association of intensity of patient quality of life in relation to pain and health with total knee arthroplasty. Material and Method: A cross-sectional analysis was carried out. among 159 patients of total knee arthoplasty. Data was collected from patients of total knee arthroplasty in the physiotherapy department of PSRD, Mayo hospital and Ghurki Trust teaching center through a standardized Questionnaire (Pain by Visual Analogue Scale and QOL by Worldwide Organization for Health quality of life questionnaire). Data entered to SPSS for statistical Analysis. Chi Square test was performed to check the Association between Pain Intensity, Health Related Quality of Life among patients with total knee arthoplasty. Results: Among 159 participants with total knee arthoplasty, 14(8.8%) were with no-pain, 41(25.8%) were with mild pain, 62(39.0%) were with moderate pain and 42(26.4%) were with worst pain. Quality of life was severely affected among 9(5.7%), effected among 96(60.4%) and normal among 54(34.0%). There was significant association between pain and overall quality of life, as well as physical, psychological, social, and environmental factors, As the P value was 0.045, 0.017, 0.032, 0.032 and 0.017 respectively, which was <0.05 which means that there was significant association between Pain and overall Quality of Life. Conclusion: There was significant association between pain and quality of life including physical, psychological, social relations and environmental quality of life, as quality of life was affected among patients with moderate and worst pain.